A Gender-based Study of Apology Strategies Employed by Indonesian Students - Sandyarini Melati Irawan; Tofan Dwi Hardjanto (Universitas Gadjah Mada, 2021)
This study investigates the apology strategies used by Indonesian university students and examines whether there is any gender difference in the apologies made by these students. The data were collected using Discourse Completion Task (DCT) containing eight situations. The DCT was distributed to 42 English Department students comprising 21 female students and 21 male students. Altogether, 336 apology utterances were collected. The results showed that the students most frequently used a combination of apology strategies (68.4%), especially a combination of Illocutionary Force Indicating Device (IFID) and Explanation or Account of Cause (EoC). Furthermore, there seems to be no difference in the types of strategies used by female and students. Both groups tended to use a combination strategies and IFID. However, in terms of intensity, female students tended to apologize more intensely than the males and this was evident from their more frequent use of apology intensifications.